Ethnic Kurdish Revolutionary Movement for the Formation of Democratic Confederalism in the Region of Rojava - Sikky, Rahmat (Papua Journal of Diplomacy and International Relations, 2025)
The ethnic Kurds play a critical role in the formation of the Democratic Confederalism government in the autonomous region of Rojava. For decades, they have faced oppression and disenfranchisement in Turkey, Syria, Iran, and Iraq. However, the present article focuses on the Kurds of Syria, given that the formation of the current autonomous government of Rojava is in an area that used to be territorially under the authority of Syria. This article aims to explain the revolutionary movement of the Kurds and the conflicts they experienced until encountering the concept of democratic confederalism. Using a qualitative method, this article argues that the Kurdish ethnic revolutionary movement is an ideological movement that utilizes the concept of democratic confederalism as a response to systemic oppression by the state. The concept is derived from Abdullah Ocalan’s anarchist ideology, inspired by Murray Bookchin. It promotes inclusivity and diversity in governance and adopted as a model of governance in Rojava which allows the active participation of various religious, ethnic, and minority groups in political, economic, democratic, and governmental processes.  KEYWORDS  Ethnic Kurds;  Democratic  Confederalism;  Revolutionary Movement; Rojava